Determining Spatial Typology Through Visitor Perception for Apitourism Facility in Malaysia - Mustaffa, Muhammad Izzat Irfan; Shaari, Mariam Felani; Zaman, Nurulhusna Qamaruz (MAJ - Malaysia Architectural Journal, 2022)
The Malaysian beekeeping industry is an important and integral component of the agricultural sector, providing additional income to farmers and indirectly producing food for the population through pollination services. To enhance more experience of bee life towards public community, apitourism emerges as a tourism that offers visitors adventure on way of life in beekeeping industry. But the perception of visitors on apitourism facility in Malaysia have been skeptical with the issues of convenience and safety of the facility and also the low quality of space that cannot give deeper interaction between visitor and bee environment. A successful apitourism facility can be executed by aiming to understand the visitor need based on their perception toward apitourism facility in Malaysia which to initiate better spatial typology required to enhance visitor experience in future. This paper intends to analyse visitor perception on apitourism facility in Malaysia to initiate better spatial typology, to enhanced visitor experience. The objectives from this dissertation are to study the purpose of apitourism facility, to analyse visitor survey within set of variables based on their perception toward apitourism facility and to initiate and determine spatial typology required for better visitor experience. Qualitative questionnaire was developed to collect primary data, assessing the perception of visitors which led to the determination of spatial typology needed by future visitor on apitopurism facility.